[OP.7C.06] THE PREVALENCE OF CENTRAL HYPERTENSION AND ITS ASSOCIATION WITH TARGET ORGAN DAMAGE IN COMMUNITY-DWELLING ELDERLY CHINESE: THE NORTHERN SHANGHAI STUDY. (September 2017) - Yu, S.; Zhang, Y.; Xu, Y.; Blacher, J.; Xiong, J.; Lv, Y.; Bai, B.; Chi, C.; Teiliewubai, J.
Abstract : Objective: To investigate the prevalence of central hypertension and its association with target organ damage (TOD). Figure. No caption available. Design and method: 869 community-dwelling participants without taking anti-hypertensive agents, derived from the Northern Shanghai Study cohort, were recruited for this analysis. Brachial and central BP were measured by mercury sphygmomanometer and SphygmoCor (AtCor Medical, Australia), respectively. Brachial and central hypertension were defined as brachial BP> = 140/90 mmHg and central BP> = 130/90 mmHg. Asymptomatic TOD including left ventricular mass index (LVMI), ratio of transmitral early diastolic peak flow and early diastolic movement (E/Ea), carotid intima-media thickness (CIMT), carotid-femoral pulse wave velocity (CF-PWV), estimated glomerular filtration rate (eGFR) and urinary albumin/creatinine ratio (UACR), were all evaluated. Results: The 869 participants (70.6 ± 5.7 years, men 43.8%) included 495(57.0%) participants with brachial and central consistent normotension, 44(5.1%) isolated brachial hypertension, 24(2.8%) isolated central hypertension and 306(35.2%) brachial and central combined hypertension. Compared to participants with brachial and central normal BP level, participants with isolated central hypertension presented faster CF-PWV (8.07 VS. 8.97, P < 0.05) and greater UACR (32.32 VS. 59.96, P < 0.05). Compared to participants with isolated brachial hypertension, participants with brachial and central combined hypertension presented higher E/Ea ratio (8.77 VS. 10.18, P < 0.05). Conclusions: The central hypertension is prevalent and more than 90% of them are combined with brachial hypertension in this elderly Chinese cohort. Isolated central hypertension is associated with worse vascular and renal damage, which implies that those with normal brachial but elevated central BP perhaps should be considered for anti-hypertensive therapy.